The Association Between Orofacial Pain and Depression: A Systematic Review - Anita H; Asnely Putri F; Maulina T (Journal of Pain Research, 2024)
Hadia Anita,1 Farah Asnely Putri,2 Tantry Maulina2,3 1Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 3Dentistry Department, Faculty of Medical Sciences, Radboud University, Nijmegen, the NetherlandsCorrespondence: Tantry Maulina, Dentistry Department, Faculty of Medical Sciences, Radboud University, Philips van Leydenlaan 25, Nijmegen, 6525 EX, the Netherlands, Tel +31 650019232, Email tantry.maulina@radboudumc.nl; tantry.maulina@unpad.ac.idBackground: The occurrence of orofacial pain is often accompanied by comorbid conditions such as depression. Even though previous studies suggested a bidirectional correlation between orofacial pain and psychological factors, some studies still provided contradictory results.Objective: This systematic review aimed at providing scientific evidence regarding the association between orofacial pain and depression in published literature.Methods: The current study is a systematic literature review (PROSPERO registration no. CRD42023438596) that was conducted by reviewing cross-sectional studies that investigated the association between orofacial pain and depression. Article selection was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidance. Articles searching was performed by using three databases, namely PubMed, ScienceDirect, and Scopus using the Boolean operator method. Article screening was carried out by applying the inclusion and exclusion criteria, as well as duplication checking, suitability checking, and compatibility checking. Reviewed articles went through the risk of bias evaluation form from the Joanna Briggs Institute (JBI). Extracted data were analyzed in a qualitative method.Results: Twelve studies that were conducted on 5557 participants were included in the final review. After all articles were analyzed, the correlation between orofacial pain and depression was revealed. Most articles revealed a positive correlation between orofacial pain and depression, and the rest showed how orofacial pain patients showed significantly higher depression scores compared to those individuals without orofacial pain.Conclusion: The results of this systematic review suggested a correlation between orofacial pain and depression with varying degrees. Incorporating potential depressive symptoms’ treatment, when treating orofacial pain patients, should be part of the treatment plan.Keywords: pain, orofacial pain, depression, correlation